DI-013 Pharmaceutical intervention on switching treatment from intravenous to oral antibiotics. (24th February 2014) - Bosó-Ribelles, A; Moregó-Soler, A; Nájera-Pérez, MD; Bosó-Ribelles, V; Arribas-Diaz, B; Sánchez-Martínez, I; Sánchez-Catalicio, MM; Selvi-Sabater, P; Manresa-Ramon, N; Rizo-Cerdá, AM
Abstract : Background: Conversion from intravenous (IV) to oral treatment has many advantages, such as avoiding the adverse events attributed to IV treatment and using less costly drugs. It is also more comfortable, requires fewer human resources and it potentially shortens the length of hospital stay. However it is very important not to have any contraindication for oral treatment. The drugs involved must have excellent bioavailability following oral administration. Purpose: To evaluate the results of a pharmaceutical intervention on switching sequentially from IV to oral antibiotics. Materials and methods: Prospective and comparative study, carried out over 3 months (between March and May 2012); consisted of a phase of observation and another phase of intervention. We collected demographic data, diagnosis, antibiotic dosage and treatment duration, signs and symptoms related to the infection improving and oral tolerance to medicines and nutrition. We selected all the patients on IV treatment with levofloxacin, ciprofloxacin, metronidazole and clindamycin. Over the intervention phase and after 48–72 h of the intravenous treatment, we consulted the physician for approval to switch to the oral drug. Statistical analysis was performed using SPSS 19.0 Results: 140 patients were involved. 44 in the observation phase and 96 in the intervention phase. Mean age was 72.8 (95% CI 66.0–79.6) and 71.8 years old (95% CI 68.5–75.7) respectively. Main diagnoses were divided into these infections: respiratory, gastrointestinal, urinary tract and other. During observation phase these were as follows: respiratory 24 (54.5%), gastrointestinal 10 (22.7%), urinary tract 2 (4.5%) and other 8 (18.1%). During intervention phase the numbers were: 45 (46.8%), 21 (21.8%), 6 (6.25%) and 24 (25%) respectively. In the observation phase, IV treatment duration was 6.5 days (interquartile range, 3–11) and it reduced to 4 days (interquartile range, 3–9) in the intervention phase (p = 0.068). A tendency was seen in the number of days of IV administration to decrease. Conclusions: Pharmaceutical intervention reduces length of IV treatment. Therefore, a pharmacist-managed intravenous to oral step down system may be a good tool to reduce costs and potential adverse events attributed to IV treatment. This could be an example of the importance of pharmaceutical care in hospitalised patients. No conflict of interest.